Synergistically optimized electrical and thermal properties by introducing electron localization and phonon scattering centers in CuGaTe2 with enhanced mechanical properties. Issue 22 (11th May 2020) - Huang, Lulu; Zhang, Jian; Zhu, Chen; Ge, Zhenhua; Li, Yuanyue; Li, Di; Qin, Xiaoying
Abstract : CuGaTe2 based chalcopyrite materials have attracted intense research interest due to their high power factor. Abstract : CuGaTe2 based chalcopyrite materials have attracted intense research interest due to their high power factor. However, it is difficult to substantially improve the thermoelectric performance because of their high thermal conductivity. Here we simultaneously optimize their thermoelectric and mechanical properties by introducing carbon particles (CPs) into the CuGaTe2 matrix. Firstly, as electron localization centers, the introduced carbon particles can enhance their electrical conductivity and thereby the power factor by adjusting the electrical transport properties. Secondly, the interfaces between carbon particles and the matrix can strongly scatter the heat carrying phonons and suppress their thermal conductivity, leading to ∼41% decrease in lattice thermal conductivity at 873 K. The highest ZT value (∼1.0@873 K) is obtained for CuGaTe2 + 0.5 wt.% CPs, which is ∼28% larger than that of pure CuGaTe2 . Thirdly, the softer carbon particles can simultaneously optimize the hardness and fracture toughness of the composites, which is beneficial for the techniques used in the processing of thermoelectric devices. The hardness is decreased from 4.45 to 3.82 GPa and the fracture toughness is increased from 0.80 to 1.10 MPa m 1/2 after introducing 0.5 wt.% CPs into the CuGaTe2 matrix, respectively. All results indicate that the incorporation of carbon particles is a very promising approach for improving the thermoelectric and mechanical properties of CuGaTe2 .